Performance assessment of the ALBIRA II pre-clinical SPECT S102 system for 99mTc imaging - Attarwala, Ali Asgar; Hardiansyah, Deni; Romanó, Chiara; Jiménez Franco, Luis David; Roscher, Mareike; Wängler, Björn; Glatting, Gerhard (Annals of nuclear medicine, 2021)
The performance characteristics of the SPECT sub-system S102 of the ALBIRA II PET/SPECT/CT are analyzed for the 80 mm field of view (FOV) to evaluate the potential in-vivo imaging in rats, based on measurements of the system response for the commonly used Technetium-99 m (99mTc) in small animal imaging.